Comparison of the efficacy of low doses of methylprednisolone, acetaminophen, and dexketoprofen trometamol on the swelling developed after the removal of impacted third molar - Eroglu, Cennet-Neslihan (Med Oral Patol Oral Cir Bucal, 2015)
BACKGROUND: The aim of the present study was to compare the efficacy of low doses of methylprednisolone, acetaminophen and dexketoprofen trometamol, which are among the drug groups used in our clinic, on postoperative swelling developing after removal of impacted third molar. MATERIAL AND METHODS: The three group of patients received either 40 mg methylprednisolone or 300 mg acetaminophen or 12.5 mg dexketoprofen trometamol one hour before the procedure, according to the patient groups. The patients in the methylprednisolone group were injected with methylprednisolone at a dose of 20 mg 24 hour after the procedure and prescribed 300 mg acetaminophen as rescue analgesic. During the postoperative period, the doses that were given before the procedure were continued 3 times a day for 2 days in the acetaminophen and dexketoprofen trometamol groups. Maximal swelling was assessed preoperatively and at the postoperative 48 hours by ultrasound images. RESULTS: Swelling was 34% lower in the methylprednisolone than in the other groups; however, no statistically significant difference was found between the groups. The acetaminophen and dexketoprofen trometamol groups exhibited clinical results close to each other. CONCLUSIONS: Combination of low doses of methylprednisolone and acetaminophen provide a safe and adequate clinical success on swelling. Key words: Methylprednisolone, acetaminophen, dexketoprofen trometamol, third molar extraction, swelling.